2020
DOI: 10.1590/1807-1929/agriambi.v24n4p238-243
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and mepiquat chloride can affect fiber quality and cotton yield

Abstract: The use of mepiquat chloride (MC) in cotton (Gossypium hirsutum L.) cultivation has increased significantly in recent years. The use of MC, a growth regulator, results in higher precocity and lower height and consequently increases yield and reduces crop costs. The objective of this study was to evaluate the effects of nitrogen (N) and MC doses on fiber quality and cotton yield. This study was conducted during the 2012/13 and 2013/14 harvests in the experimental area of the Fundação de Apoio à Pesquisa Agropec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Previous studies showed that micronaire value and irrigation levels are negatively correlated (Sobrinho et al, 2015;Pinnamaneni et al, 2021). Higher irrigation or nitrogen causes immature fiber (Leal et al, 2020). This result could be attributed to the more vegetative growth and less reproductive growth under the higher irrigation level (Pinnamaneni et al, 2021).…”
Section: Cotton Qualitymentioning
confidence: 94%
“…Previous studies showed that micronaire value and irrigation levels are negatively correlated (Sobrinho et al, 2015;Pinnamaneni et al, 2021). Higher irrigation or nitrogen causes immature fiber (Leal et al, 2020). This result could be attributed to the more vegetative growth and less reproductive growth under the higher irrigation level (Pinnamaneni et al, 2021).…”
Section: Cotton Qualitymentioning
confidence: 94%
“…Therefore, in the cultivation and planting of cotton, the grower should not only focus on the management of water and fertilizer in the field [ 4 , 5 ], but should also consider the use of exogenous plant hormones for chemical regulation [ 6 ] for reasonable control of cotton growth and development. This will determine the shape of the ideal plant type [ 7 ] by reducing plant height [ 8 ], shorten the main stem and fruiting branch internodes [ 9 , 10 ], improve light transmittance, reduce boll shedding [ 11 ], and promote boll opening [ 12 ] to improve economic yield [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most Brazilian cotton crops are sown in wide row spacings (0.75–0.90 m) with populations ranging from 50,000 to 130,000 plants ha −1 . Under these conditions, management of growth regulators is mostly performed via foliar spraying (Echer & Rosolem, 2017; Leal et al., 2020). However, there is no consensus regarding appropriate application rates, especially for early sprays (Pinhead square stage).…”
Section: Introductionmentioning
confidence: 99%
“…Low MC rates can lead to uncontrolled growth, especially for cultivars in the late reproductive stage in highly fertile soil (Echer & Rosolem, 2017; Leal et al., 2020). High rates can result in temporary growth disruptions.…”
Section: Introductionmentioning
confidence: 99%